Overcoming species barriers: an outbreak of Lagovirus europaeus GI.2/RHDV2 in an isolated population of mountain hares (Lepus timidus) ... - Neimanis, Aleksija; Ahola, Harri; Larsson Pettersson, Ulrika; Lopes, Ana; Abrantes, Joana; Zohari, Siamak; Esteves, Pedro; Gavier-Widén, Dolores (figshare, 2018)
Abstract Background Prior to 2010, the lagoviruses that cause rabbit hemorrhagic disease (RHD) in European rabbits (Oryctolagus cuniculus) and European brown hare syndrome (EBHS) in hares (Lepus spp.) were generally genus-specific. However, in 2010, rabbit hemorrhagic disease virus 2 (RHDV2), also known as Lagovirus europaeus GI.2, emerged and had the distinguishing ability to cause disease in both rabbits and certain hare species. The mountain hare (Lepus timidus) is native to Sweden and is susceptible to European brown hare syndrome virus (EBHSV), also called Lagovirus europaeus GII.1. While most mountain hare populations are found on the mainland, isolated populations also exist on islands. Here we investigate a mortality event in mountain hares on the small island of Hallands Väderö where other leporid species, including rabbits, are absent. Results Post-mortem and microscopic examination of three mountain hare carcasses collected from early November 2016 to mid-March 2017 revealed acute hepatic necrosis ...